The neuroscience in breast cancer: Current insights and clinical opportunities - Jia-feng Wang; Meng-chuan Wang; Lei-lei Jiang; Neng-ming Lin (Heliyon)
The involvement of nerves in the development of breast cancer has emerged as a significant factor. Interaction between the nervous system and breast cancer can influence tumor initiation, growth, invasion, metastasis, reverse resistance to drugs, promote inflammation in tumors, and impair the immune system's ability to combat cancer. This review examined the intricate relationship linking the nervous system with breast cancer, emphasizing both central and peripheral aspects of the nervous system. Moreover, we reviewed neural cell factors and their impact on breast cancer progression, alongside the interactions between nerves and immunology, microbiota in breast cancer. Furthermore, the study discussed the potential of nerves as biomarkers for diagnosing and prognosticating breast cancer, and evaluated prospects for improving chemotherapy and immunotherapy therapeutic outcomes in breast cancer treatment. We hope to provide a deeper understanding of the neurobiological underpinnings of breast cancer and pave the way for the discovery of innovative therapeutic targets and prognostic markers.